Fungal Exposure and Asthma: IgE and Non-IgE-Mediated Mechanisms - Zhang, Zhonghua (Curr Allergy Asthma Rep, 2016)
Fungi are ubiquitous in indoor and outdoor environments and have been associated with respiratory disease including childhood and adult asthma. A growing body of evidence from human and animal studies has revealed a link between fungal exposure, especially indoor fungal exposure, with asthma initiation, persistence, and exacerbation. Despite the overwhelming evidence linking mold exposure and asthma, the mechanistic basis for the association has remained elusive. It is now clear that fungi need not be intact to impart negative health effects. Fungal components and fungal fragments are biologically active and contribute to asthma development and severity. Recent mechanistic studies have demonstrated that fungi are potent immunomodulators and have powerful effects on asthma independent of their potential to act as antigens. This paper will review the connection between fungal exposure and asthma with a focus on the immunological mechanisms underlying this relationship.